Study on the Absorption and Conduction Properties of Vanisulfane in Tobacco - Xingang Meng; Fei Li; Qian Huang (Journal of Chemistry)
The purposes of this study were to explore the systemic properties of vanisulfane in tobacco plant and to provide a reference for the rational use of vanisulfane in the field. After the tobacco plants were treated by hydroponics and foliar spraying, the contents of vanisulfane in root and stem leaf were detected by high-performance liquid chromatography tandem high-resolution mass spectrometry (UPLC-HRMS), and the position of vanisulfane in root and stem leaf was real-time observed through fluorescence two-photon confocal microscope. UPLC-HRMS results showed that the contents of vanisulfane in root and stem leaf gradually increased with the extension of processing time, and after 12 h treatment, the contents of vanisulfane in root and stem leaf reached the maximum levels of 31.95 and 0.215 mg/kg, respectively. In addition, fluorescence two-photon confocal microscope results showed that vanisulfane could observe in the root and stem leaf. These results showed that vanisulfane had excellent upward and downward of systemic in tobacco plants, which is helpful to guide a reference for the rational use of vanisulfane in the field.